Analysis of the pile-to-cap connection of pile caps on two steel piles – An experimental and numerical study. (1st February 2022) - Gonçalves, Vítor Freitas; Delalibera, Rodrigo Gustavo; de Oliveira Filho, Márcio Alves
Highlights: There is a lack of consensus in literature regarding the strength of nodal regions. Complementary reinforcement did not influence the bearing capacity. Traditional strut-and-tie models lead to conservative results for steel piles. Abstract: The objective of this research was to study the mechanical behavior of pile caps on two steel piles submitted to centered loading with different arrangements of the connection between pile and pile cap, as well as evaluate analytical models found in the technical literature. A numerical analysis of a pile cap on two steel piles was performed using the software ANSYS®, which was compared to the experimental results from Tomaz (2018) [22]. From the parameters defined on the numerical analysis, 63 other numerical models were developed. An analysis of variance of the results obtained pointed out that the variables that had an impact on the bearing capacity of the pile cap were the embedment length of the pile and the compressive strength of the concrete. An experimental program with three models of full-scale pile caps on two steel piles were executed, in which the type of arrangement of the connection between pile and pile cap varied. The types of arrangement studied were bars welded onto the steel piles and bars welded onto the steel piles along with stirrups. The type of arrangement had no impact on the bearing capacity of the pile cap. The analytical model from Meléndez et al. (2019) [12] was the most precise on predicting the ultimate load of the pile caps. The criteria from ABNT NBR 6118:2014 [5] that characterizes the behavior of pile caps was not adequate as it does not consider the inclination of the strut, which is one of the main parameters of design.